Comparison of the Risks and Benefits Between Iron Sucrose and Ferric Carboxy Maltose in Anemic Pregnant Females - Farzana Aamir, Erum Memon, Hina Memon, Sanober Memon, Sana Alvi, Hina Ali (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Iron deficiency anemia is one of the most common complications in pregnancy, associated with significant maternal and fetal morbidity. Objective: To compare the risks and benefits of ferric carboxymaltose and iron sucrose in the treatment of iron deficiency anemia among pregnant females. Methods: This prospective comparative study was conducted in the department of Obstetrics and Gynaecolgy, Jinnah Medical and Dental College, Karachi from March 2023 to August 2023. A total of 200 pregnant women diagnosed with iron deficiency anemia were included in the study. Participants were randomly allocated into two groups: Group A (n = 100) received intravenous ferric carboxymaltose, and Group B (n = 100) received intravenous iron sucrose. Baseline demographic and clinical data were recorded. Hemoglobin and serum ferritin levels were measured before treatment and at 3–4 weeks post-therapy. Results: Baseline characteristics were comparable between the two groups. The mean rise in hemoglobin was significantly higher with ferric carboxymaltose (2.74 ± 0.42 g/dL) compared to iron sucrose (1.59 ± 0.34 g/dL, p < 0.001). Serum ferritin increased in both groups, with a greater rise in the iron sucrose group (113.9 ± 44.4 ng/mL) than ferric carboxymaltose (101.7 ± 42.4 ng/mL, p = 0.005). Adverse effects were less frequent in the ferric carboxymaltose group (nausea 9%, vomiting 5.5%, abdominal pain 3.5%) compared to the iron sucrose group (nausea 21.5%, vomiting 20.5%, abdominal pain 27%, all p < 0.05). Conclusion: Ferric carboxymaltose was more effective in rapidly improving hemoglobin levels and was better tolerated, while iron sucrose produced a slightly greater increase in ferritin stores but with higher rates of adverse effects. Keywords: Iron deficiency anemia, pregnancy, ferric carboxymaltose, iron sucrose, hemoglobin, ferritin